PENERAPAN APLIKASI QUIZIZZ TERHADAP HASIL PEMBELAJARAN TEKS CERAMAH PADA SISWA SMK KELAS XI - Deli Siti Maulida; Wikanengsih; Heri Isnaini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The use of technology in the world of education is an effort to encourage renewal so that there is compatibility between the development of the times, learning and students' interests. One of the ICT-based applications used in learning is the quiziz application, which is used as a medium for learning evaluation tools. The purpose of this study was to describe the results of students' responses to the use of the quiziz application on the learning outcomes of class XI Vocational High School students in lecture text material. This study used descriptive qualitative method. The subject taking technique used was purposive sampling, which was taken randomly while the instrument used was a questionnaire. Based on the results of the research that has been done, it is known that the average percentage of effectiveness is 83% in the very good category. Thus it can be concluded that the use of the quiziz application in learning lecture texts can increase student motivation, provide a new atmosphere in the implementation of exams, besides that the design and features in the application are fun so as to attract students' attention.